2022
DOI: 10.1001/jamaoto.2021.4048
|View full text |Cite
|
Sign up to set email alerts
|

Association of Multiprofessional Preoperative Assessment and Information for Patients With Head and Neck Cancer With Postoperative Outcomes

Abstract: IMPORTANCE Multidisciplinary perioperative assessment for patients undergoing complex oncologic head and neck cancer (HNC) surgery is widely implemented. However, to our knowledge, the association of multiprofessional preoperative assessment, information, and briefing with postoperative outcomes has not been evaluated. OBJECTIVE To compare postoperative complications, length of hospital stay (LOS), readmissions, mortality, and costs per case among patients undergoing complex oncologic HNC surgery before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Several groups have developed enhanced recovery after surgery (ERAS) pathways with targeted perioperative interventions to improve length of stay in HNSCC patients undergoing free flap reconstruction 53 . Intensive preoperative counseling has been shown to decrease the length of stay and reduce readmissions in high risk HNSCC patients 54–56 . Our data suggest that hypothyroid patients may benefit from programs to decrease the risk of readmission.…”
Section: Discussionmentioning
confidence: 78%
“…Several groups have developed enhanced recovery after surgery (ERAS) pathways with targeted perioperative interventions to improve length of stay in HNSCC patients undergoing free flap reconstruction 53 . Intensive preoperative counseling has been shown to decrease the length of stay and reduce readmissions in high risk HNSCC patients 54–56 . Our data suggest that hypothyroid patients may benefit from programs to decrease the risk of readmission.…”
Section: Discussionmentioning
confidence: 78%
“…While there are clear psychological benefits to improving patient education, until recently, there were no publications in the HNC literature showing improved surgical outcomes from education intervention. Schmid et al recently found shorter LOS, reduced complications, and decreased cost after implementation of a preoperative multi‐professional assessment and information day (MUPAID) 42 . At this time, it is unknown which aspect of the MUPAID resulted in these improvements.…”
Section: Resultsmentioning
confidence: 99%
“…A small randomized trial by Longobardi et al showed that pre‐laryngectomy counseling by SLP increased patient satisfaction scores, decreased psychological distress, and facilitated greater use and acceptance of tracheoesophageal speech 49 . SLP counseling was included in the MUPAID protocol and may have played a contributory role in the improved outcomes 42 …”
Section: Resultsmentioning
confidence: 99%
“…Schmid et al explored the association of multiprofessional preoperative assessment and information with postoperative outcomes for patients with head and neck cancer. The magnitude of the differences in the distribution of characteristics at admission between patients in the intervention group and in the control group was compared using both standardized and nonstandardized effect sizes.…”
Section: Nonstandardized and Standardized Effect Sizesmentioning
confidence: 99%